Isozyme Polymorphism for Genetic Purity Testing in Muskmelon(Cucumis melo) hybrid - GEETA BASSI; J.S. KANWAR (Seed Research, 2026)
The study was deliberated with the objective of applying electrophoresis for determining the genetic purity of hybrid seed of muskmelon (Punjab hybrid) and its parents MS-1 (female parent) and Hara Madhu (male parent). It was observed that there was no isozyme polymorphism with respect to four isozymes ie. peroxidase, esterase, phospho-gluco-isomerase and phospho-gluco-mutase that can be applied for genetic purity testing. Therefore, it is suggested that other isozymes may be explored than these four isozymes.